Exposure of thermoelectric power-plant workers to volatile organic compounds from fuel oil: Genotoxic and cytotoxic effects in buccal epithelial cells - Garcia, Patrícia (2013)
Copyright © 2012 Elsevier B.V. All rights reserved.